ANALYSIS OF OFF-TASK BEHAVIOR IN BEHAVIORISM PERSPECTIVE - Supriatna, Muhammad Wildan; Widiastuti, Haning Tri; Putri, Nadia Amelia; Nisa, Az-Zahra Khoirul; Hasna, Cahya Fitri (Jurnal Bikotetik (Bimbingan dan Konseling: Teori dan Praktik), 2025)
This study is motivated by the presence of disruptive behaviors in the learning process, specifically off-task behavior. Off-task behavior refers to disruptive actions performed by students during the learning process, where they are not engaged in the lesson itself. Off-task behavior consists of three aspects: verbal, motoric, and passive. These behaviors occur due to various factors, one of which is behavior formation, a concept discussed within the behaviorism approach. This study explores effective strategies to reduce off-task behavior in classroom learning through the behaviorism approach. The results indicate that methods such as reinforcement, self-control, individual counseling with behavior contracts, sociodrama, self-control, and token economy enhance student engagement and create a productive learning environment. Implementation challenges include limited facilities and curriculum pressure. Collaboration between teachers, counselors, and the school is key to success. Keywords: Off-task behavior, behaviorism.